Toxicity effect of sub-chronic oral administration of class bitters® - a polyherbal formula on serum electrolytes and hematological indices in male Wistar albino rats - Kingsley C. Patrick-Iwuanyanwu; Kpobari W. Nkpaa (MDPI AG, 2015)
The indiscriminate administration of readyto- use herbal formulations has become a major concern due to their potential health risk. The study investigated the effect of class bitters® (CB) - a polyherbal formula prepared with Mondia whitei, Khaya senegalensis, Capparis erythrocarpus, Thoningia sanguinea and Xylopia aethiopica on serum electrolytes and hematological parameters in male Wistar albino rats. Two doses (500 and 1000 mg kg-1) of the polyherbal drugs were administered orally to male Wistar albino rats for a period of 9 weeks. The results showed that administration of 500 and 1000 mg kg-1 body weight of CB recorded a marked increase in the levels of sodium and chlorum when compared with control. However, there was a marked reduction in the levels of potassium and hydrogen carbonate. The results of the study also showed a significant (P≤0.05) decrease in the level of hematological parameters such as hemoglobin (Hb), packed cell volume (PCV), red blood cells (RBCs) and platelets levels in the male Wistar albino rats, when compared with control. The marked decrease in Hb, PCV, RBCs and platelets concentrations observed in experimental rats in this study suggest that CB may have an adverse effect on erythropoiesis. These observations therefore showed that long-term administration of CB might cause renal disease and anemia.